2021
DOI: 10.3390/v13061123
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Long-Term Neurodevelopmental Impact of Prenatal Zika Virus Infection in a Rat Model Using a High Resolution, Longitudinal MRI Approach

Abstract: Since Zika virus (ZIKV) first emerged as a public health concern in 2015, our ability to identify and track the long-term neurological sequelae of prenatal Zika virus (ZIKV) infection in humans has been limited. Our lab has developed a rat model of maternal ZIKV infection with associated vertical transmission to the fetus that results in significant brain malformations in the neonatal offspring. Here, we use this model in conjunction with longitudinal magnetic resonance imaging (MRI) to expand our understandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Although multiple rodent models of ZIKV exist (15)(16)(17)(18)(19), NHP models of ZIKV and fZIKV remain best suited for modeling human neurological and psychological development because of both limitations of the rodent models and strengths of the NHP model. NHPs, such as monkeys from the genus Macaca, demonstrate transplacental transmission of the ZIKV to the fetus (20)(21)(22)(23) and also share many homologies in terms of cortical structure and function with humans (24).…”
Section: Introductionmentioning
confidence: 99%
“…Although multiple rodent models of ZIKV exist (15)(16)(17)(18)(19), NHP models of ZIKV and fZIKV remain best suited for modeling human neurological and psychological development because of both limitations of the rodent models and strengths of the NHP model. NHPs, such as monkeys from the genus Macaca, demonstrate transplacental transmission of the ZIKV to the fetus (20)(21)(22)(23) and also share many homologies in terms of cortical structure and function with humans (24).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in this issue contributed to our knowledge of congenital Zika virus infection, with manuscripts utilizing animal models in rats and nonhuman primates, and a human clinical study. A new rat model of prenatal Zika virus infection described novel automated atlas-based segmentation of MR images and found that prenatal Zika virus infection alters the growth of brain regions throughout neonatal and juvenile ages [1]. A nonhuman primate model of prenatal Zika virus infection explored the impact of maternal Dengue virus immunity on neonatal development, identifying that maternal Dengue virus immunity exacerbates Zika-induced visual orientation and tracking deficits [2].…”
mentioning
confidence: 99%